Forestry-Based Flood Mitigation and Residents’ Well-Being in South-Western Nigeria - Adebayo Samson Adeoye; Ismail Olabisi Azeez (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
Flooding’s impacts are well-known, but environmental consequences in South-Western Nigeria and alternatives to costly engineering solutions must be examined. Hence, assessing residents’ perception of flooding on social well-being and forestry-based mitigation approaches in flood-prone communities of South-western Nigeria. A four-stage sampling approach was adopted for the study. The first three stages involved strategic selection in the Nigerian states of Oyo, Ogun, and Lagos, where two Local Government Areas (LGAs) were chosen in each state, leading to 22 communities in each of the LGAs, based on past flood incidences. In stage four, a household listing was used to select 250 households for questionnaire administration in 2021 systematically. Using the following analytical tools, data were analysed using descriptive statistics, ranking, and chi-square at α0.05. Findings revealed that majority of residents (72.8%) were indigene, have been resident in the flood-prone locality for at least 16 years (52.4%), married (74.4%), aged between 21 and 50 years (78.4%) and living in households of between 5 and 8 persons (62.8%). Furthermore, residents’ well-being indicators reveal significant shortcomings, except for positive social connections, education, and sanitation facilities trends. The study also identified tree planting, tree conservation in the upland areas, sustenance of the natural environment, and stabilisation of stream banks using vegetation as a nature-based solution to flood mitigation, depending on residents’ indigeneity, years of residing in the study community, and marital status. To ensure sustainable forestry practices that mitigate floods in the study area, it is crucial to have environmental and forestry agencies involved.